Collision cell pressure effect on CID spectra pattern using triple quadrupole instruments: a RRKM modeling. (29th January 2013) - Ichou, Farid; Lesage, Denis; Machuron‐Mandard, Xavier; Junot, Christophe; Cole, Richard B.; Tabet, Jean‐Claude
Abstract : Control of the ion internal energy in mass spectrometry is needed to establish a workable mass spectral library. The purpose of this study is to understand and to compare the pressure effects on the collision‐induced dissociation (CID) spectrum pattern recorded using triple quadrupole instruments. The monoprotonated Leucine enkephalin [YGGFL, H + ] was used as a thermometer molecule to calibrate the electrospray ionization (ESI) and the CID internal energies deposited on the molecular species and the time scale of ion decompositions. The survival yield and the ratio of a4 /b4 fragment ions were mainly monitored. The energy uptake for the ESI source geometry used in our study has no impact on the CID spectrum fingerprint. The collision cell pressure for the [YGGFL, H + ] has a major influence on the SY curves slope and on the experimental time scale. To demonstrate the pressure effect on internal energy distribution, three models (threshold, thermal and collisional) based on RRKM theory were built using the Masskinetics software. As a result, the limit of each model is discussed, and the investigation demonstrates that the thermal model, using truncated Maxwell‐Boltzmann internal energy distribution, is well‐suited for simulating the experimental data at high pressure widely used in the analytical conditions. Copyright © 2013 John Wiley & Sons, Ltd.